Exercise affects glutamate receptors in postsynaptic densities from cortical mice brain - Dietrich, Marcelo O.; Mantese, Carlos E.; Porciuncula, Lisiane O.; Ghisleni, Gabriele; Vinade, Lúcia; Souza, Diogo O.; Portela, Luis V. (Brain research, 2005)
Physical activity has been proposed as a behavior intervention that promotes mental health and some of the benefits induced by exercise have been related to the glutamatergic system. Indeed, glutamate is the most abundant excitatory neurotransmitter in brain. Thus, we evaluated if voluntary exercise in mice could modulate glutamatergic synapses at level of postsynaptic density (PSD). Through Western blot, we found that exercise during 1 month increased glutamatergic-related protein content in PSD from cortex of mice. Exercise increased the immunocontent of GluR1 (129%), SAP-97 (179%), GRIP-1 (129%), and in less extent, GluR2/3 (118%) and PSD-95 (112%) proteins. The overall content of NMDA subunits R1, R2A and R2B were not altered in mice that had exercised, however, the phosphorylated NMDA subunits, phospho-NMDAR1 (150%), and phospho-NMDAR2B (183%) showed a strong increase. Because exercise increased the content of phosphorylated forms of NMDA receptors, we evaluated the binding of MK-801, a specific ligand that binds to open NMDA channel. Exercise increased the binding of MK-801 in cortical cellular membranes in 51%. Altogether, our results point to a modulation of glutamatergic synapses by exercise with likely implications in the exercise-induced mental health.